Gender Structures, Strategies, and Expectations during Nepal’s Labor Migration - Reisman, Andrea Robin (My University, 2019)
Temporary migratory work has long been an adaptive response to concentrated material deprivation. As technological advances make transnational labor movements more accessible, and uneven economic development and growing global inequality boost the possible gains from migrant work, this phenomenon may become an even more salient feature of labor economies. Such migration flows are often gendered; when primarily men migrate, women in these contexts must decide whether and how to fill the labor gaps their husbands have left behind and to make sense of what this means for their social positions. Though we understand some of the ways such migration trends might matter for social transformation in migrants’ homelands, we know little about when and how men’s migration corresponds with changing beliefs about women’s household roles when women take on absent men’s labor. I use qualitative, ethnographic, and quantitative methodologies to investigate these dynamics in Nepal’s Chitwan district, a region where substantial flows of men are temporarily migrating to work in the Persian Gulf, Malaysia, and India. As women take on these new roles and responsibilities in their families, they experience increased work burdens and pressure. This may lead to changes in the gendered division of household labor, disrupting customary gender norms in households and families. The first empirical chapter of this work explores the relationship between the social structures of ethno-caste and educational attainment with traditional beliefs about sources of men’s and women’s household authority. This chapter uses mixed methodology to show that ethno-caste and education are associated with different patterns of beliefs and framing of those beliefs about household authority. The second empirical chapter examines women’s strategic decision-making during men’s absence to show how there is a difference between making decisions and claiming household power and authority and that women navigate a complex set of social expectations and practical needs during men’s absence. The third empirical chapter builds on these two findings about structure and agency to examine patterns of expansion and restrictions of gendered expectations during men’s migration. This paper shows how broadening and narrowing gender expectations exist in tandem and explores how this varies in two social sites, the household and in localized markets. Overall, this dissertation advances knowledge not only about changes in gender relations during large-scale social transformations like labor migration, but also the ways complex social and economic environments can create both opportunity and constraints.
Thesis (Ph.D.)--University of Washington, 2018
Keywords: Gender; Household Labor; Migration; Nepal; Sociology; South Asian studies; Sociology